2019
DOI: 10.14786/flr.v7i3.503
|View full text |Cite
|
Sign up to set email alerts
|

Measuring academic learning and exam self-efficacy at admission to university and its relation to first-year attrition

Abstract: Self-efficacy is associated with both academic performance and attrition in higher education. Whether it is possible to measure students' academic self-efficacy after admission and prior to commencing higher education (i.e. pre-academic self-efficacy) in a valid and reliable way has hardly been studied. Aims: 1) to evaluate the construct validity and psychometric properties of two short scales to measure Pre-Academic Learning Self-Efficacy (PAL-SE) and Pre-Academic Exam Self-Efficacy (PAE-SE) using Rasch measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…It is also the outcome of the interplay of several cognitive and non-cognitive factors. Specifically, the GPA has been expressed as an effect of personality traits, self-efficacy, motivation, learning strategies, achievement goals, study skills, and study habits [52][53][54]. Studies have observed that when students' intentions to withdraw is controlled, the impact of the variables that explain attrition-except the GPA-becomes insignificant [19,51].…”
Section: Proposed Research Model and Hypothesis Formulationmentioning
confidence: 99%
“…It is also the outcome of the interplay of several cognitive and non-cognitive factors. Specifically, the GPA has been expressed as an effect of personality traits, self-efficacy, motivation, learning strategies, achievement goals, study skills, and study habits [52][53][54]. Studies have observed that when students' intentions to withdraw is controlled, the impact of the variables that explain attrition-except the GPA-becomes insignificant [19,51].…”
Section: Proposed Research Model and Hypothesis Formulationmentioning
confidence: 99%
“…The performance improvement program is aim at increasing teacher self-efficacy (Trauth-Nare, 2015), building motivation (S. Huang et al, 2019), and developing teachers' metacognitive (Colognesi et al, 2019). Self-efficacy is important because it is specific, and it is easy to develop (Nielsen et al, 2019). It is the tool to provide opportunities for researchers or policymakers to develop teacher selfefficacy through several workshops and training.…”
Section: Teacher's Tpack Value and Employment Statusmentioning
confidence: 99%